Nickel-Promoted Catalysts in the Reforming of n-Butane with CO or HO - Monika Pańczyk; Grzegorz Giecko; Wojciech Gac; Sylwia Pasieczna; Beata Stasińska; Tadeusz Borowiecki (Adsorption Science & Technology)
Studies of the reforming of n-butane by steam and carbon dioxide have been undertaken employing commercial catalysts such as Ni/α-Al 2 O 3 modified by small additions of promoters such as K, Ba, Ce, W and Mo compounds. It was found that promoters improved the resistance of the catalyst towards coking, with this effect being smaller where CO 2 was employed in the reforming reaction than when steam was used. The dynamics of the growth of the carbon deposit on the catalyst surface depended on the promoters employed as well as on the operating conditions; however, in the CO 2 reforming of n-butane, such coking was more pronounced than in steam reforming. Use of the TPO method with oxygen or CO 2 did not reveal considerable differences between the coke deposits formed during the reforming of n-butane with CO 2 or H 2 O on the catalysts examined.